Measuring depressive symptoms during adolescence: what is the role of gender? - Bulhões, C (2017)
Aims. The higher prevalence of depressive symptoms among females is well recognised but the reasons for this gender difference are not fully understood. There is growing evidence that current diagnostic criteria and instruments used to assess depression are less sensitive to depression in men, but studies about this issue among adolescents are scarce, especially in Latin countries. Our aim was to assess sex differences in the intensity of depressive symptoms, measured using the Beck Depression Inventory second edition (BDI-II), among Portuguese adolescents, at 13 and 17 years of age. Methods. Urban adolescents born in 1990 and enrolled in schools of Porto, Portugal, in 2003–2004 (EPITeen study) completed the BDI-II at 13 and 17 years of age. The final sample included 1988 (52.2% girls) and 2131 (53.0% girls) adolescents at 13 and 17 years, respectively. Sex differences in the frequency of endorsing the statements on the 21 items of the BDI-II were examined using the χ2 test and effect sizes were estimated (Cohen’s w). To examine whether responses were linked systematically to sex, we used a differential item functioning (DIF), based on the logistic regression approach. Option characteristic curves were estimated for items with differential endorsement and a new BDI-II score was computed excluding those items. Results. Girls and boys at the same level of depression expressed similar severity ratings for most of the depressive symptoms. We had four items with DIF at 13 and 17 years of age. At 13 years, two items provided lower scores (sadness and crying items) and two higher scores (punishment feelings and loss of interest in sex items) among boys, comparing with equally depressed girls. At 17 years, the four items with DIF provided lower scores among boys (sadness, crying, self-dislike and tiredness or fatigue items). After excluding these items the prevalence of depression remained higher among girls but at 17 years the difference between sexes was attenuated. Conclusions. Sex differences were found in the functioning of the BDI-II, more relevant at 17 years of age, which may lead to an overestimation of symptoms among girls as well as to lower reported rates of depression among boys. For a higher diagnostic accuracy it is important that the criteria and instruments used to assess depression adequately reflect female and male common symptoms and experiences of depression.